Effect of apalutamide on health-related quality of life in patients with non-metastatic castration-resistant prostate cancer: an analysis of the SPARTAN randomised, placebo-controlled, phase 3 trial. Issue 10 (October 2018) - Saad, Fred; Cella, David; Basch, Ethan; Hadaschik, Boris A; Mainwaring, Paul N; Oudard, Stéphane; Graff, Julie N; McQuarrie, Kelly; Li, Susan; Hudgens, Stacie; Lawson, Joe; Lopez-Gitlitz, Angela; et al.
Summary: Background: In the SPARTAN trial, addition of apalutamide to androgen deprivation therapy, as compared with placebo plus androgen deprivation therapy, significantly improved metastasis-free survival in men with non-metastatic castration-resistant prostate cancer who were at high risk for development of metastases. We aimed to investigate the effects of apalutamide versus placebo added to androgen deprivation therapy on health-related quality of life (HRQOL). Methods: SPARTAN is a multicentre, international, randomised, phase 3 trial. Participants were aged 18 years or older, with non-metastatic castration-resistant prostate cancer, a prostate-specific antigen doubling time of 10 months or less, and a prostate-specific antigen concentration of 2 ng/mL or more in serum. Patients were randomly assigned (2:1) to 240 mg oral apalutamide per day plus androgen deprivation therapy, or matched oral placebo plus androgen deprivation therapy, using an interactive voice randomisation system. Permuted block randomisation was used according to the three baseline stratification factors: prostate-specific antigen doubling time (>6 months vs ≤6 months), use of bone-sparing drugs (yes vs no), and presence of local-regional nodal disease (N0 vs N1). Each treatment cycle was 28 days. The primary endpoint was metastasis-free survival. The trial was unblinded in July, 2017. In this prespecified exploratory analysis we assessed HRQOL using the Functional Assessment of Cancer Therapy-Prostate (FACT-P) and EQ-5D-3L questionnaires, which we collected at baseline, day 1 of cycle 1 (before dose), day 1 of treatment cycles 1–6, day 1 of every two cycles from cycles 7 to 13, and day 1 of every four cycles thereafter. This study is registered withClinicalTrials.gov, numberNCT01946204 . Findings: Between Oct 14, 2013, and Dec 15, 2016, we randomly assigned 1207 patients to receive apalutamide (n=806) or placebo (n=401). The clinical cutoff date, as for the primary analysis, was May 19, 2017. Median follow-up for overall survival was 20·3 months (IQR 14·8–26·6). FACT-P total and subscale scores were associated with a preservation of HRQOL from baseline to cycle 29 in the apalutamide group; there were similar results for EQ-5D-3L. At baseline, the mean for FACT-P total score in both the apalutamide and placebo groups were consistent with the FACT-P general population norm for US adult men. Group mean patient-reported outcome scores over time show that HRQOL was maintained from baseline after initiation of apalutamide treatment and was similar over time among patients receiving apalutamide versus placebo. Least-squares mean change from baseline shows that HRQOL deterioration was more apparent in the placebo group. Interpretation: In asymptomatic men with high-risk non-metastatic castration-resistant prostate cancer, HRQOL was maintained after initiation of apalutamide treatment. Considered with findings from SPARTAN, patients who received apalutamide had longer metastasis-free survival and longer time to symptomatic progression than did those who received placebo, while preserving HRQOL. Funding: Janssen Research & Development.